Use of Internet and Learning Habits of Students in Universities within Ile-Ife Metropolis, Osun State, Nigeria - Ojo Olumuyiwa Emmanuel; Ajibare Oluwaseun Oluropo; Oguntoye Folasade Busayo (International Journal of Media and Communication Research, 2024)
The use of the Internet has become an essential tool for students to pursue their educational interests and to excel in their learning habits. This study investigated the influence of internet use on the learning habits of students in universities within Ile-Ife Metropolis, Osun State, Nigeria. A descriptive survey was conducted among 168 students in selected tertiary institutions. Two research questions guided this study. A self-administered questionnaire through an online platform was used to collect data. Mean scores were used for data analysis. The findings of the study revealed that there was a high influence of internet use on learning habits amongst the students, and the use of online learning platforms and online library resources played a major role as a form of internet usage in improving the learning habits of the respondents (3.36 and 3.44 respectively). However, the following conclusions were drawn from the result: there is a high use of the internet by students in selected universities within Ile-Ife Metropolis; internet usage had a significant positive influence on the learning habits of students as they spent most of their time on academic activities and the use of online learning platforms and online library resources was the best tool for improving learning habits among the students